The system of training elite cross-country racers while getting ready for the Olympic Games 2022 (PRC, Beijing) - Batalov, A. G.; Burdina, M. E.; Khitrova, A. A. (The Russian Journal of Physical Education and Sport, 2022)
The article is connected with the model characteristics (parameters) revelation of effective individualized competitions systems among the winners of the Olympic Games (OG) 2022 in cross-country skiing. Materials. Studying competitive practice of elite skiers in World Cup (WC) starts 2021/22 and the results of the Olympic Games in cross-country skiing 2022 in Beijing (PRC). Research methods: Information sources analysis and summarizing, competitions protocols of the official calendar of the World Cup (WC) 2021/22 and the official records of the Olympic Games results in cross-country skiing 2022 analysis, methods of mathematical statistics. Results. As results of the research we revealed the main characteristics of competitions systems among the winners of OG-2022 in individual disciplines of cross-country skiing among men and women. We defined the individualized model parameters of the effective competitions systems, conditioned by competitive specialization: there are three of them - marked sprinting (Sundling J., Sweden), distant (Johaug T., Norway, Niskanen I., Finland) and universal (Bolshunov, Russia, Klaebo J., Norway). We also defined the failure of Russian male and female teams in terms of sports-technical result of the winners in individual races. The failure of the individual sprint participants in the qualifying round among men was 2,68%, among women - 6,97%, in skiathlon - 6,09% and 4,7%, in the race with the separate start - 3,27% and 3,65%, in mass-start race (marathon) - 0,33% and 4,79%. Conclusion. Competitions systems organization during the period of training for OG-2022 among the winners in the individual disciplines of cross-country skiing can be considered as effective individualized models of training for the main International starts.